Assessment of gaseous ozone treatment on Salmonella Typhimurium and Escherichia coli O157:H7 reductions in poultry litter. (November 2020) - Chang, Ruixue; Pandey, Pramod; Li, Yanming; Venkitasamy, Chandrasekar; Chen, Zhao; Gallardo, Rodrigo; Weimer, Bart; Jay-Russell, Michele; Weimer, Bart
Highlights: Increase in moisture resulted in the increased survival of S. Typhimurium in poultry litter. Increase in the moisture content reduced the effect of ozone in eliminating pathogens. Extended exposure time resulted in increase in pathogen inactivation. Low ozone concentrations (<6%) and low exposure time was not effective in pathogen inactivation in poultry litter. Gaseous O3 treatment has a potential to be used as decontamination technique for animal wastes. Abstract: Poultry litter is used as soil amendment or organic fertilizer. While poultry litter is enriched with organic matter suitable for land, the presence of pathogens such as Salmonella in poultry litter is a concern. To investigate the effect of gaseous ozone on pathogen reductions in poultry litter, this study conducted a series of experiments that involved understanding of Salmonella Typhimurium and Escherichia coli O157:H7 inactivation at various doses of Ozone (O3 ) in wet and dry poultry litter conditions. Previously, ozone treatment has been shown to disinfect the surface of foods and plant materials including fruits, juices, and wastewater, however, additional research are needed to better understand the impacts of ozone on treatment of soil amendments. Sanitizing methods capable of eliminating pathogens of soil amendments are crucial to mitigate disease outbreaks related with litter/manure-based fertilizers. In this study, a bench scale continuous ozone treatment system was designed to produce O3 gas, with a range O3 concentrations (7.15–132.46 mg·L −1 ), monitor ozone concentrations continuously, and control the ozone exposure time (15 to 90 mins) to understand the effectiveness of O3 in eliminating S. Typhimurium and E. coli O157:H7 in poultry litter. Results showed that 7.15 mg·L -1 did not reduce the counts of S. Typhimurium until exposure to O3 for 90 min. The O3 concentrations of 43.26 132.46 mg·L -1 exposure reduced the bacterial counts. Furthermore, the moisture content of poultry litter was found to be an influencing factor for pathogen reduction. The pathogen reduction rates were reduced when the moisture content was increased. At higher moisture content, high concentrations of O3 (132.46 mg·L -1 ) were needed for pathogen reductions. The moisture content of 30% or lower was found to be more effective for controlling pathogen levels in poultry litter. Our study demonstrates that gaseous O3 treatment could be used as an additional decontamination technique to ensure the certain degree of microbiological safety of poultry litter based soil amendment.